Education And Training Management In An Effort To Improve The Quality Of Educators At SMA Muhammadiyah 3 Yogyakarta - Annisa Yolanda; Tumin Tumin (Journal on Education, 2024)
The management of education is an effort related to educational activities in which the process influences and motivates student creativity using tools, methods, media, facilities, and infrastructure needed to hold the educational activities. This research aims to describe the management of education and training in SMA Muhammadiyah 3 Yogyakarta. The researcher used a qualitative method with a descriptive qualitative approach. The researcher observed and interacted directly with the headmaster and teachers through interviews, observation, and documentation. In testing the validity, he used the triangulation technique. The data obtained were then analyzed by conducting data reduction, data presentation, and conclusion. The research results showed that the administration, management planning of education in SMA Muhammadiyah 3 Yogyakarta, and national standard of education became the guidance of management administration in the school. The training was given to educational staff following the needs observed by the headmaster and vice headmaster of the curriculum by inviting experts and giving challenges to the teachers going to participate in the training. The headmaster gave rewards to the teachers who had finished their research. The participation of the teachers in the training was great because it was related to the level of career that the educators would have so that they became participative in developing potential. The enhancement of the quality of the educational staff in SMA Muhammadiyah 3 Yogyakarta was with various trainings and programs covering MGMP, workshops, double expertise program, and other supervision program development. By participating in the training, the educational staff of SMA Muhammadiyah 3 Yogyakarta can develop their potential or skills starting from pedagogy competence, professional competence, and personality competence.